Defining Agile Organizational Infrastructure in Traditional Project Management Context : Organizational Culture Perspective on Utilizing Agile Ways of Working - Koski, Hanna (My University, 2024)
In today’s rapidly changing VUCA environment organizations are increasingly challenged by the need for adaptability. This has evoked an interest in agile ways of working, originated in the IT industry, and now spreading as a broad movement across various sectors. This research examines the agile paradigm from the organizational viewpoint, focusing on organizational agility and governance to determine how agile ways of working could be utilized within different organizational contexts. The research began with a literature review to establish the theoretical framework. After that followed an empirical study that utilized the Organizational Culture Assessment Instrument (OCAI), based on the Competing Values Framework. This study was conducted within a Case Organization, and the employees involved evaluated their current and preferred organizational cultures, providing an understanding and insights in regard to applying agile ways of working. The findings suggest that there is now one correct way for organizations to be agile, and therefore each organization needs to assess and find its own ways of applying agile ways of working. The empirical results suggest that the Case Organization needs an urgent shift from the currently over-dominant Market-oriented culture towards a more balanced culture, however with an emphasis on Clan and Adhocracy values. Furthermore, especially in areas of Management of Employees, Organizational Glue, and Strategic Emphasis, there was a strong emphasis on agile ways of working in the sense of focusing more on people-centered approaches and prioritizing employees’ well-being. It is also to be addressed that, Hierarchy – offering stability and structure – was notably present across all areas which emphasizes the Case Organization’s need and desire as well for the traditional ways of working. To conclude, this research emphasizes the importance of aligning agile ways of working with organizational culture to enhance adaptability and responsiveness, suggesting that for an organization to be agile it needs to effectively integrate both – stable and dynamic – elements within the organizational infrastructure.

Nykyisessä jatkuvasti muuttuvassa toimintaympäristössä organisaatioiden muutoskyvykkyyden tarve on kasvanut. Tämä on lisännyt kiinnostusta niin sanottuja ketteriä – agile-menetelmiä – kohtaan, jotka alun perin kehittyivät IT-alalla ja ovat sittemmin levinneet laajalti yli toimialarajojen. Tässä tutkimuksessa tarkastellaan agile-menetelmien hyödyntämistä organisaatiotason näkökulmasta, keskittyen erityisesti organisaatiorakenteiden ja kulttuurin näkökulmaan. Tutkimus alkaa kirjallisuuskatsauksella, jonka tavoitteena on luoda tutkimuksen teoreettinen viitekehys. Tämän jälkeen seuraa empiirinen tutkimus, joka hyödyntää kilpailevien arvojen viitekehykseen perustuvaa OCAI-työkalua (Organizational Culture Assessment Instrument). Tutkimus on toteutettu Case Organisaatiossa, jonka työntekijät arvioivat OCAI-työkalua hyödyntäen organisaation nykyistä ja ihanteellista organisaatiokulttuuria, tarjoten näkemyksiä ja pohjan agile-menetelmien soveltamiselle. Tutkimustulokset osoittavat, että ei ole olemassa vain yhtä oikeaa tapaa toteuttaa organisaation ketteryyttä, vaan jokaisen organisaation on löydettävä omaan kontekstiinsa ja kulttuuriin sopivat toimintatavat. Empiiriset tulokset paljastavat, että Case Organisaatiolla on tarve siirtyä kiirreellisesti markkinadominoivasta kulttuurista kohti klaani- ja adhokratia-vetoista kokonaisuudessaan tasapainoista kulttuurirakennetta. Lisäksi etenkin Työntekijöiden hallinnan, Organisaatiota sisäisesti yhdistävän voiman ja Strategisten painotusten osa-alueilla korostetaan ihmiskeskeisen johtamisen ja työntekijöiden hyvinvoinnin priorisoinnin merkitystä, jotka ovat suorasti liitettävissä agile-menetelmien ominaispiirteisiin. Samalla tutkimus tuo esille, että hierarkia, joka tarjoaa organisaatioiden toimintaan vakautta ja rakenteita, on merkittävästi läsnä kaikilla osa-alueilla. Tämä osoittaa Case Organisaation tarpeen ja halun säilyttää myös perinteiseksi miellettyjä toimintatapoja. Tutkimuksen yhteenvetona voidaan todeta agile-menetelmien ja organisaatiokulttuurin yhteensovittamisen tärkeyttä, jotta organisaatio voi aidosti parantaa muutoskyvykkyyttään ja reagointivalmiuttaan. Organisaatiorakenteiden osalta tämä edellyttää vakaiden ja dynaamisten elementtien oikeasuhdanteista hyödyntämistä.
Keywords: agile methods; ketterät menetelmät; organisaatiokulttuuri; projektinhallinta; kulttuurianalyysi; fi=Julkisjohtaminen|en=Public Management|; fi=Hallintotieteiden maisteriohjelma|en=Master's Programme in Administrative Sciences|